UJI AKTIVITAS ANTIOKSIDAN DAUN BAWANG MEKAH (Eleutherine americana Merr.) DENGAN METODE DPPH (2,2-DIFENIL-1-PIKRILHIDRAZIL) - Dina Pratiwi; Sri Wahdaningsih; Isnindar Isnindar (Faculty of Pharmacy, Universitas Gadjah Mada, 2013)
Use and demand of traditional medicinal plants currently growing in the direction that research in traditional medicines have also increased. One of the plants that is efficacious as a medicine is bawang mekah (Eleutherine americana Merr.). This plant is usually used by people as a traditional medicine to treat various diseases. This study aims to determine the antioxidant activity of bawang mekah leaves. Antioxidant activity assays performed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) that begins with the extraction by maceration. Dry leaves of bawang mekah (150 g) was soaked with ethanol 70% for 3x24 hours at room temperature. The liquid extract obtained is evaporated by rotary evaporator and waterbath till viscous extracts is obtained. Then to extract performed phytochemical screening and preliminary test with DPPH method by thin layer chromatography (TLC) with a mobile phase BAA (4:1:5). The antioxidant activity was measured using a UV-Vis spectrophotometer and compared with vitamin C. The results of the phytochemical screening showed the extract contains flavonoids, saponins, phenols and tannins. In preliminary tests using KLT, gained 3 spots visualized with UV light 366 nm and sprayed with 0.2% DPPH. Third spot showed changes color to yellow with purple background that indicating the extract positive has antioxidant activity. The results of spectrophotometric measurements showed that the extract has the IC50 at 31.97437 ug/ml, whereas vitamin C had a lower IC50 value (3.90186 ug/ml).